Soil and geography are more important determinants of indigenous arbuscular mycorrhizal communities than management practices in Swiss agricultural soils. Issue 8 (24th March 2014) - Jansa, Jan; Erb, Angela; Oberholzer, Hans‐Rudolf; Šmilauer, Petr; Egli, Simon
Abstract Arbuscular mycorrhizal fungi (AMF) are ubiquitous soil fungi, forming mutualistic symbiosis with a majority of terrestrial plant species. They are abundant in nearly all soils, less diverse than soil prokaryotes and other intensively studied soil organisms and thus are promising candidates for universal indicators of land management legacies and soil quality degradation. However, insufficient data on how the composition of indigenous AMF varies along soil and landscape gradients have hampered the definition of baselines and effect thresholds to date. Here, indigenous AMF communities in 154 agricultural soils collected across Switzerland were profiled by quantitative real‐time PCR with taxon‐specific markers for six widespread AMF species. To identify the key determinants of AMF community composition, the profiles were related to soil properties, land management and site geography. Our results indicate a number of well‐supported dependencies between abundances of certain AMF taxa and soil properties such as pH, soil fertility and texture, and a surprising lack of effect of available soil phosphorus on the AMF community profiles. Site geography, especially the altitude and large geographical distance, strongly affected AMF communities. Unexpected was the apparent lack of a strong land management effect on the AMF communities as compared to the other predictors, which could be due to the rarity of highly intensive and unsustainable land management in Swiss agriculture. In spite of the extensive coverage of large geographical and soil gradients, we did not identify any taxon suitable as an indicator of land use among the six taxa we studied.